PENGARUH PENGGUNAAN MEDIA DIORAMA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA DI SANGGAR BELAJAR KEPONG MALAYSIA - Vivi Juli Indah Purnama; Amin Basri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Conventional learning practices that rely heavily on teacher-centered approaches and lack the use of concrete learning media can hinder the development of students’ creative thinking skills. Therefore, innovative learning strategies are needed to actively engage students and provide meaningful learning experiences. This study aims to examine the effect of using diorama media on students’ creative thinking skills at Sanggar Belajar Kepong, Malaysia. The research employed a quantitative approach using a quasi-experimental method with a One Group Pretest–Posttest Design. The research subjects consisted of a single group of students who were administered a pretest prior to the treatment and a posttest after learning activities using diorama media. Data were collected through tests and observations, while data analysis was conducted using the Shapiro–Wilk normality test and a dependent t-test. The results indicated that the data were normally distributed and that there was a significant difference between pretest and posttest scores after the implementation of diorama media. These findings demonstrate that the use of diorama media has a significant effect on improving students’ creative thinking skills. Diorama media creates a more interactive, concrete, and meaningful learning environment, encouraging students to develop ideas, imagination, and active participation during the learning process. Therefore, diorama media can be considered an effective alternative instructional medium for enhancing students’ creative thinking skills.